Duhovnost v literaturi - Valens, Mea (Jezik in slovstvo, 2002)
In everyday life and in the professional circel of different dields of scuencethe word "spiritual" is often used inconsistently and its meaning is not accurately defined. The paper sets bounds to the use of the term "spiritual" on the basis of Eastern and Western philosophy and limits it to phenomena that are connected, not with human body and mind, but with the soul.Examples of its occurrence in Slovene poetry are given.
Keywords: duhovnost; duh; duša; transcendenca; slovenska poezija; semantics; semantika